Straight - Francis, Dick. (Boston, Mass. : G.K. Hall, 1990)
Derek is thrust into trouble and danger after the death of his brother. His only hope of survival is to identify the enemy.
Kirkus Review.
Young Adult.
Young Adult
Keywords: Horse racing -- Fiction; Large type books; Large print books; Mystery fiction; Detective and mystery stories